2022
DOI: 10.24271/psr.2021.309110.1096
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices on COVID-19 in the Kurdistan Region of Iraq: An Online Cross-Sectional Survey

Abstract: Background: First COVID-19 case was recorded on February (26 th , 2020) in Kurdistan Region of Iraq (KRI). Shortly after that number of cases increased significantly but, limited research has been conducted to assess the knowledge, attitudes, and practices of the population in the region about the pandemic. Objectives: The objective of this study was to gain a better understanding of the people's awareness and their attitude towards the pandemic by conducting a knowledge, attitude and practice (KAP) survey. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
2
Order By: Relevance
“…A few studies carried out respectively in Egypt, India and Iran showed similar findings. 3,6,13,22 Contrary to our findings, some studies in Africa found that a significant number of chronic disease patients had poor knowledge of and practices towards COVID-19. 2,23 This difference in knowledge is perhaps because after the fourth wave of COVID-19, at the time of this study in South Africa, most of the population had more information on COVID-19 than in other countries.…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies carried out respectively in Egypt, India and Iran showed similar findings. 3,6,13,22 Contrary to our findings, some studies in Africa found that a significant number of chronic disease patients had poor knowledge of and practices towards COVID-19. 2,23 This difference in knowledge is perhaps because after the fourth wave of COVID-19, at the time of this study in South Africa, most of the population had more information on COVID-19 than in other countries.…”
Section: Discussioncontrasting
confidence: 99%
“…The degree of knowledge (KAP level = 74.95%) about COVID-19 reported in the present study is higher than the studies done on Indian population (50%),[ 4 ] Iraq (52.15%),[ 5 ] and Syria (60%)[ 6 ] and lower than the studies done in China (90%)[ 7 ] and Greater Noida, Uttar Pradesh, India (81%). [ 8 ] These differences observed were mainly due to the educational status of the participants and the period during which the studies were carried out.…”
Section: Discussioncontrasting
confidence: 78%
“…These studies in different countries revealed that the results differed among nations and were impacted by the types of human settlements. As a result, while creating health programs for COVID-19 and any future epidemics or pandemics, health and education agencies in various nations should strengthen their preventative measures by building specialized measures aimed at individuals in different settlements [76][77][78][79][80][81][82][83]. Knowledge disparity has been extensively studied in health communication.…”
Section: Discussionmentioning
confidence: 99%